Granulometric properties of particles in Upper Miocene sandstones from thin sections, Szolnok Formation, Hungary - Király, Csilla; Falus, György; Gresina, Fruzsina; Jakab, Gergely; Szalai, Zoltán; Varga, György (Hungarian Geographical Bulletin, 2019)
Particle size and shape are among the most important properties of sedimentary deposits. Objective and robust determination of granulometric features of sediments is a challenging problem, and has been standingin the focal point of sedimentary studies for many decades. In this study, we provide an overview of a new analytical approach to characterize particles from thin sections of sandstones by using 2D automated optical static image analysis. The analysed samples are originated from the turbiditic Lower Pannonian (Upper Miocene) sediments of Szolnok Formation. Sandstone samples were analysed from 1,500 to 2,250 m depth range. According to the previous studies: the detrital components are quartz, muscovite, dolomite, K-feldspar and plagioclase. Diagenetic minerals are mostly carbonates (calcite, Fe-dolomite, ankerite, siderite), clay minerals (illite, kaolinite), ankerite, siderite and kaolinite. As the discussed Szolnok Formation is considered as a potential CO2 storage system (to reduce atmospheric CO2 concentration), special attention has to be paid on grain size and shape alteration evaluation, since pore water-rock interactions affected by CO2 injection may cause changes in particle properties.The primarily aim of the present study was to develop a method for effective characterization of the particle size and shape of sandstones from thin sections. We have applied a Malvern Morphologi G3SE-ID automated optical static image analyser device, what is completed with a Raman spectrometer. Via the combined analysis of granulometry and chemical characterization, it was obvious that there were specific relationships among various grain shape parameters (e.g., circularity values correlate to width and length ratios, as well as to convexity) and the results indicated that based simply on particle shapes, muscovites can be effectively separated from other minerals. Quartz and feldspar grains showed the highest variability in shapes as these are detrital ones, and sometimes arrived as lithic fragments from which other parts were dissolved The size and shape of carbonate minerals depends highly on the original pore size and shape because these minerals are mainly diagenetic. The shape of detrital dolomites depends on diagenetic ankerite, as it replaces the rim of dolomites.